Silver Ecotoxicity Estimation by the Soil State Biological Indicators - S. I. Kolesnikov; N. I. Tsepina; L.V. Sudina; T. V. Minnikova; K. Sh. Kazeev; Yu. V. Akimenko (Applied and Environmental Soil Science)
The use of silver in various spheres of life and production leads to an increase in environmental pollution, including soil. At the same time, the environmental consequences of silver pollution of soils have been studied to a much lesser extent than those of other heavy metals. The aim of this study is to estimate silver ecotoxicity using the soil state biological indicators. We studied soils that are significantly different in resistance to heavy metal pollution: ordinary chernozem (Haplic Chernozems, Loamic), sierosands (Haplic Arenosols, Eutric), and brown forest acidic soil (Haplic Cambisols, Eutric). Contamination was simulated in the laboratory. Silver was introduced into the soil in the form of nitrate in doses of 1, 10, and 100 mg/kg. Changes in biological parameters were assessed 10, 30, and 90 days after contamination. Silver pollution of soils in most cases leads to deterioration of their biological properties: the total number of bacteria, the abundance of bacteria of the genus Azotobacter, the activity of enzymes (catalase and dehydrogenases), and the phytotoxicity indicators decrease. The degree of reduction in biological properties depends on the silver concentration in the soil and the period from the contamination moment. In most cases, there is a direct relationship between the silver concentration and the degree of deterioration of the studied soil properties. The silver toxic effect was most pronounced on the 30th day after contamination. In terms of their resistance to silver pollution, the studied soils are in the following order: ordinary chernozem > sierosands ≥ brown forest soil. The light granulometric composition of sierosands and the acidic reaction of the environment of brown forest soils, as well as the low content of organic matter, contribute to high mobility and, consequently, high ecotoxicity of silver in these soils. The regional maximum permissible concentration (rMPC) of silver in ordinary chernozem (Haplic Chernozems, Loamic) is 4.4 mg/kg, in sierosands (Haplic Arenosols, Eutric) 0.9 mg/kg, and in brown forest soils (Haplic Cambisols, Eutric) 0.8 mg/kg.